Rubble, ruins and romanticism : visual style, narration and identity in German Post-War cinema - Moeller, Martina (Film studies, 2013)
Examines the so-called rubble films, usually seen as simplistic texts reaffirming "good Germans during bad times" views, finding in some of them visual and narrative romantic discourse which provokes critical discussion on German national identity in the wake of the Third Reich